The Effect of Ozonation Process on Bromide-Containing Groundwaters in Bandung Area and Its Surroundings - Syafila, Mindriany; Sukandar, Sukandar; Haryanto, Eric (Journal of Engineering and Technological Sciences, 2012)
Disinfection process was applied as the last step of the water treatment to kill pathogenic bacteria in  the  water. However,  according to  several studies, the  ozonation  disinfection  process could form undesired by-products.  One of the by-products  potentially  affecting human life is bromate  produced from bromide ionic-containing  water. This study was carried out to examine the effect of raw water  characteristics  and  pH  on  bromate  formation.  Also,  the  performance  of bromate formation for a period of exposure time was analyzed. Raw waters taken from four different areas around Bandung were exposed to ozone introduced to a reactor with a flow rate of 2 L/min. The pH of the raw waters varied from 4, 7 to 10.  The  results  show  that  there  was  no  evidence  of  an  initial  bromide  ion concentration,  whereas  a  change  in  pH  value  gives  a  significantly  different outcome. In  acidic condition  (pH of 4) the  bromate  formation tends to decrease, whereas  when  the  pH  value  increases  to  a  pH  of  10,  the  bromate  formation increases.  Therefore, for drinking water  with a  neutral pH,  when bromide ions are  detected  in  the  raw  water,  the  drinking  water  may  be  toxic  due  to  the presence of bromate.